Manajemen Mutu Madrasah Ibtidaiyah Hijriyah II Palembang - Syaiful Akhyar (Studia Manageria, 2020)
The existence of MI HijriyahII Palembang was in one of the rooms at the bottom of the Hijriyah mushollah which was used as a place of learning for the children around it. Over time the number of students is increasing and is known by the surrounding community and has a positive impact on the progress of education, especially for madrasa-loving education in the city of Palembang. This study aims to understand the concept of quality management from the planning and organizing aspects carried out in MI Hijriyah II Palembang and analyze the commitment of the madrasa civitas in maintaining and improving the quality of education. This research is evaluative in nature, which interprets the data created and compiled in a comprehensive and systematic manner designed to answer questions, test or prove hypotheses. Data collection techniques using observation, interviews and documentation, then presented in triangulation with data reduction steps, data display and data verification, after the data collected then analyzed with qualitative descriptive techniques. To guarantee the quality of the madrasa as an educational institution in order to develop a variety of creativity, science, and knowledge, especially those relating to teacher competencies that include pedagogical competencies, personality competencies, social competencies and professional competencies, the madrasas need to form a madrasah teacher communication forum, so that competencies the quality of teachers in madrasas can be improved.